Description of a remarkable new species of Isoperla (Plecoptera: Perlodidae), with supplements for Isoperla kozlovi Zhiltzova, 1972 from China - Chen, Zhi-Teng; Du, Si-Kai; Li, Xin-Tong (Zootaxa, 2021)
A remarkable new species of Isoperla Banks, 1906, Isoperla chongxui sp. nov. from Henan Province of China is described and illustrated. The new species is characterized by the conspicuous abdominal tergal processes in males. Comparisons are made between the new species and its congeners. New descriptions and illustrations are provided for Isoperla kozlovi Zhiltzova, 1972 from northeastern China. Isoperla fengi Wu & Claassen, 1934 and Isoperla curvispina (Wu, 1938) are considered nomen dubia due to lost types and poor original descriptions.